(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
A study was conducted to evaluate the effect of inclusion levels of ginger on milk yield and composition of Red Sokoto does. A total of twenty-eight (28) Red Sokoto does (RSD) weighing on the average 16.29 kg were used. The animals were randomly assigned to four diets, containing 0, 250, 500 and 750g/100kg diet levels of ginger respectively in a completely randomized design. Each of the animals were fed concentrate at 1.5% of body weight. Milk yield and composition were recorded. Udder and teats of each doe were washed with cotton wool soaked in disinfectant (Methylated spirit) and then they were hand-milked into sterilized containers and measured using calibrated cylinder. Milk samples were analyzed for total solids, fat and protein using infrared spectrophotometry. Ash content was determined after heating in a muffle furnace for 3 hours and the solids not fat content was calculated by difference. Results obtained showed that higher total milk yield of 360 liters was recorded in RSD fed diet containing 250 g ginger. All milk composition parameters (total solid, ash, fat, solid not fat and crude protein), were significantly affected (P<0.05) by ginger inclusion. Fat and crude protein contents were significantly affected (P<0.05) by lactation stages with their higher values (P<0.05) recorded in mid lactation stage (4.35% and 3.61%) respectively. Ash content recorded significantly higher value (P<0.05) in early lactation stage (1.05%). Ginger inclusion levels in the diets of RSD improved milk yield and milk composition.